Analysis of internal combustion engine cylinder block and head cooling using nanofluid coolant - Urgancı, Kemal Burak. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
This study investigates the application of nano uids in an engine cooling system considering the complete system performance. Performance of nano uid coolants is examined in comparison with traditional coolants for a 1.5-liter diesel engine cooling system. Pure water, ethylene glycol, and 50% by volume mixture of ethylene glycol and water are considered as base uids, and nano uids with CuO, Al2O3 and hBN nanoparticles for a particle volume fraction of 0.5-3% range are investigated. System components are modeled individually and the overall cooling performance is investigated for the complete system. As a result, it is shown that Al2O3, CuO, hBN-containing nano uids have superior thermal performance with respect to their corresponding base uids as coolants. It is also shown that there exist an optimum particle volume concentration that leads to a maximum cooling performance when both increase in heat-transfer and pressure drop is considered with increasing particle volume concentration. The use of nano uids as coolants introduces opportunities such as increasing cooling capacity, reducing engine body temperature or reducing pumping power.
Keywords: Nanofluids.; Internal combustion engines -- Cooling.